Black lives matter - Edwards, Sue Bradford; Harris, Duchess (Special reports., 2016)
Explores the history of the "black lives matter" movement, beginning with the Trayvon Martin, Michael Brown, and Freddy Grey cases, the riots in Ferguson and Baltimore, and the activism messages passed around on Twitter. Explores the movement in the context of the history of the civil rights movement and the work of men like Martin Luther King, Jr.